2013
DOI: 10.1186/1129-2377-14-6
|View full text |Cite
|
Sign up to set email alerts
|

Discovery by a proteomic approach of possible early biomarkers of drug-induced nephrotoxicity in medication-overuse headache

Abstract: BackgroundMedication-overuse headache (MOH) is a chronic headache condition that results from the overuse of analgesics drugs, triptans, or other antimigraine compounds. The epidemiology of drug-induced disorders suggests that medication overuse could lead to nephrotoxicity, particularly in chronic patients. The aim of this work was to confirm and extend the results obtained from a previous study, in which we analyzed the urinary proteome of 3 MOH patients groups: non-steroidal anti-inflammatory drugs (NSAIDs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 32 publications
3
38
0
1
Order By: Relevance
“…T h e ba nd s w ho s e mo l e c u l a r w e i g ht corresponded to vitellogenin (180 kDa) and apolipophorins (250 kDa) were cut from the gels, digested in-gel with trypsin and finally analysed by a Nano LC-CHIP-MS system (ESI-Q-TOF 6520; Agilent Technologies) as previously described (Bellei et al 2013). Raw mass spectrometry data were processed to obtain the Mascot generic files for database searching.…”
Section: Protein Identification By Mass Spectrometrymentioning
confidence: 99%
“…T h e ba nd s w ho s e mo l e c u l a r w e i g ht corresponded to vitellogenin (180 kDa) and apolipophorins (250 kDa) were cut from the gels, digested in-gel with trypsin and finally analysed by a Nano LC-CHIP-MS system (ESI-Q-TOF 6520; Agilent Technologies) as previously described (Bellei et al 2013). Raw mass spectrometry data were processed to obtain the Mascot generic files for database searching.…”
Section: Protein Identification By Mass Spectrometrymentioning
confidence: 99%
“…Preclinical studies have shown that repeated or continuous treatment with antimigraine drugs result in persistent up-regulation of neurotransmitters within the orofacial division of the trigeminal ganglia and in the development of CA in response to migraine triggers, even weeks after discontinuation of the antimigraine drug [ 7 ]. In our previous study we found elevated urinary levels of Prostaglandin-H2 D-synthase (PTGDS) in 3 MOH patient groups (triptans, NSAIDs and mixture abusers) in respect to healthy non-abusers individuals as control group [ 8 ]. Prostaglandin D2 is the most abundant prostanoid produced in the central nervous system of mammals, and is implicated in the modulation of neural functions, such as sleep induction, regulation of body temperature, nociception, pain responses and allodynia [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…L-PGDS was already found at unusually high concentrations in urine of MOH patients [13,14]. The enzyme is highly expressed in leptomeninges [30] and is physiologically eliminated via the kidney.…”
Section: Discussionmentioning
confidence: 97%